2023
DOI: 10.3389/fpls.2023.1274770
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of volatile organic compounds from essential oils against the postharvest pathogens Botrytis cinerea, Monilinia fructicola, Monilinia fructigena, and Monilinia laxa

Samuel Álvarez-García,
Marwa Moumni,
Gianfranco Romanazzi

Abstract: Gray mold and brown rot, caused respectively by Botrytis cinerea and Monilinia spp., are fungal diseases responsible for significant losses during the storage of fruit and vegetables. Nowadays, the control of postharvest diseases is shifting towards more sustainable strategies, including the use of plant secondary metabolites. In this study, the antifungal activity of Origanum vulgare, Thymus vulgaris, Thymus serpyllum, Melaleuca alternifolia, Lavandula officinalis, Lavandula hybrida, Citrus bergamia, Rosmarin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Cinnamomum zeylanicum EO in the vapor phase was tested in vitro against B. cinerea, Monilinia fructicola, Monilinia fructigena, and Monilinia laxa. Based on mycelial growth inhibition, the volatiles of C. zeylanicum EO consistently showed higher inhibition against B. cinerea, suggesting a specific mode of action [37]. Vapor phase and direct contact via growth media of EOs could act differently against postharvest fungi [37,38], but this hypothesis needs confirmation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cinnamomum zeylanicum EO in the vapor phase was tested in vitro against B. cinerea, Monilinia fructicola, Monilinia fructigena, and Monilinia laxa. Based on mycelial growth inhibition, the volatiles of C. zeylanicum EO consistently showed higher inhibition against B. cinerea, suggesting a specific mode of action [37]. Vapor phase and direct contact via growth media of EOs could act differently against postharvest fungi [37,38], but this hypothesis needs confirmation.…”
Section: Discussionmentioning
confidence: 97%
“…Based on mycelial growth inhibition, the volatiles of C. zeylanicum EO consistently showed higher inhibition against B. cinerea, suggesting a specific mode of action [37]. Vapor phase and direct contact via growth media of EOs could act differently against postharvest fungi [37,38], but this hypothesis needs confirmation. On the other hand, A. alternata and, to a lesser extent, P. italicum appear to have a greater ability to tolerate the various antifungal treatments.…”
Section: Discussionmentioning
confidence: 97%
“…A summary of previous studies of carvacrol against B. cinerea, Colletotrichum spp., and Penicillium spp. is presented in Table S1 [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. Caution is advised when interpreting these results due to potential variations in isolates (or species, especially in the genus Colletotrichum and Penicillium) across diverse studies.…”
Section: Comparison Of Carvacrol Antimicrobial Activitymentioning
confidence: 99%
“…In vitro and in vivo studies demonstrated the antifungal activity of EOs against fruit postharvest pathogens, such as Botrytis cinerea [29][30][31], Penicillium expansum [32,33], Alternaria spp. [34], and Monilinia spp.…”
Section: Introductionmentioning
confidence: 99%
“…[34], and Monilinia spp. [31,35]. The antimicrobial activity of EOs has been associated with several mechanisms, including the alteration in cell wall and membrane permeability and changes in gene expression patterns [36].…”
Section: Introductionmentioning
confidence: 99%